2015
DOI: 10.1371/journal.pone.0117155
|View full text |Cite
|
Sign up to set email alerts
|

Are Movements Necessary for the Sense of Body Ownership? Evidence from the Rubber Hand Illusion in Pure Hemiplegic Patients

Abstract: A question still debated within cognitive neuroscience is whether signals present during actions significantly contribute to the emergence of human’s body ownership. In the present study, we aimed at answer this question by means of a neuropsychological approach. We administered the classical rubber hand illusion paradigm to a group of healthy participants and to a group of neurological patients affected by a complete left upper limb hemiplegia, but without any propriceptive/tactile deficits. The illusion stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 48 publications
5
97
1
Order By: Relevance
“…As compared to the classical rubber-hand setup, these three more or less continuous informational streams provide a much richer database for the computation of cross-modal contingencies. Given that these computations are considered to represent the main factor that underlies both subjective agency (Burin et al, 2015) and subjective body ownership (Armel & Ramachandran, 2003;Botvinick & Cohen, 1998), one would indeed expect that objective agency increases both subjective agency and synchrony effects. However, while objective agency clearly plays a role for subjective ownership, it is less clear whether subjective agency is relevant for subjective ownership as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As compared to the classical rubber-hand setup, these three more or less continuous informational streams provide a much richer database for the computation of cross-modal contingencies. Given that these computations are considered to represent the main factor that underlies both subjective agency (Burin et al, 2015) and subjective body ownership (Armel & Ramachandran, 2003;Botvinick & Cohen, 1998), one would indeed expect that objective agency increases both subjective agency and synchrony effects. However, while objective agency clearly plays a role for subjective ownership, it is less clear whether subjective agency is relevant for subjective ownership as well.…”
Section: Discussionmentioning
confidence: 99%
“…While earlier studies tended to consider body ownership and agency as separate components of the self (see Gallagher, 2000;Jeannerod, 2003;Tsakiris et al, 2007), there is increasing evidence that these two factors interact in producing ownership illusions (Burin et al, 2015;Dummer, Picot-Annand, Neal, & Moore, 2009;Kokkinara & Slater, 2014;Ma & Hommel, 2013Tsakiris et al, 2006Tsakiris et al, , 2007. However, the relationship between sense of ownership and sense of agency is still not clear: Some studies showed greater sense of illusory ownership with greater sense of agency, some studies showed the opposite relationship between the two senses, and some studies showed no correlation at all.…”
Section: Ownership and Agencymentioning
confidence: 99%
See 1 more Smart Citation
“…Following standard methods (Burin et al, 2015), the RHI paradigm consisted of a black box (60 cm×40 cm×20 cm) with a perpendicular panel dividing it in half (30 cm×40 cm×20 cm), arranged such that the patient’s real hand would be hidden and only the life-like rubber hand would be within the patient’s view. The patient wore a white cape on her body to ensure that only the rubber hand was in view and was oriented such that the patient’s shoulder was in line with the rubber hand.…”
Section: Methodsmentioning
confidence: 99%
“…The participant was then asked to report the number on the ruler that corresponded to her perceived index finger (Burin et al, 2015). This procedure was repeated six times, changing randomly the position of the ruler each time.…”
Section: Methodsmentioning
confidence: 99%